Labyrinthine calcification in ears with otitis media and antineutrophil cytoplasmic antibody-associated vasculitis (OMAAV): A report of two cases. Issue 2 (April 2023) - Yoshida, Tadao; Kobayashi, Masumi; Sugimoto, Satofumi; Naganawa, Shinji; Sone, Michihiko
Abstract: Otitis media with antineutrophil cytoplasmic antibody-associated vasculitis (OMAAV) has been proposed as a new type of otitis media. The hearing loss caused by OMAAV can be expected to improve with early detection and intervention, but if it continues to worsen and leads to deafness, it is challenging to recover the patient's hearing. When bilateral deafness occurs, cochlear implant (CI) surgery is the only way to improve hearing. Here, Case 1 showed unilateral cochlear calcification, and Case 2 showed bilateral cochlear calcification. In Case 1, CI surgery was performed on the ear lacking calcification, and in Case 2 it was performed on the ear with milder calcification. In Case 2, granulation was present from the tympanic space to the mastoid, the round window was closed, and the basal turn of the cochlea was narrowed. Such calcification of the cochlea caused by OMAAV has not been reported so far. It is essential to detect these changes by computed tomography scans at an early stage and to perform CI surgery at an appropriate time, because hearing improvements are not expected in patients who become deaf because of OMAAV.